(untitled) - Boone, Bardley Gilbert (Oxford, 1998)
The book covers the fundamental aspects of optical signal processing at an introductory level and also discusses more applied topics. It continues on with coverage of devices, architectures, and prominent applications.
Keywords: Optical data processing,Signal processing